OBSERVAÇÕES SÔBRE AS DOENÇAS E AGENTES PATOGÊNICOS DAS PLANTAS EM PERNAMBUCO - Campos, A. R.; Pickel, D. B. José (REVISTA DE AGRICULTURA, 2020)
OBSERVAÇÕES SÔBRE AS DOENÇAS E AGENTES PATOGÊNICOS DAS PLANTAS EM PERNAMBUCO